Geomembrane applications for controlling diffusive migration of petroleum hydrocarbons in cold region environments. (1st October 2016) - McWatters, Rebecca S.; Rutter, Allison; Rowe, R. Kerry
Abstract: Laboratory permeation tests examine the migration of aromatic hydrocarbons (benzene, toluene, ethylbenzene and xylenes (BTEX)) at 2, 7 and 14 °C through three different types of geomembrane (high density polyethylene (HDPE), linear low density polyethylene (LLDPE) and polyvinyl chloride (PVC)). Tests on both virgin and exhumed field samples provide permeation parameters (partitioning ( S gf ), diffusion ( D g ), and permeation ( P g ) coefficients) for the three geomembranes. These results are combined with published values for the same geomembranes at 23 °C to establish an Arrhenius relationship that can be used to estimate diffusion parameters at temperatures other than those for which tests were conducted. Tests on an HDPE geomembrane sample exhumed after 3 years from a landfill site in the Canadian Arctic showed no significant difference in diffusion characteristics compared to an otherwise similar unaged and unexposed HDPE geomembrane. Contaminant transport modeling for benzene through HDPE, LLPDE and PVC in a simulated landfill cover show that for the conditions examined the presence of any of the three geomembranes below the 2 m thick soil cover substantially reduced the contaminant flux compared to the soils alone for realistic degrees of saturation in the cover soil. For these same realistic cold climate cases, of the three geomembranes examined, the HDPE geomembrane was the most effective at controlling the contaminant flux out of the landfill. An increase in soil cover and liner temperature by 2 °C (from potential climate change effects) above those currently measured at an Arctic landfill showed an increase in contaminant transport through the cover system for all geomembranes due to the increase surface temperature (especially in the summer months). Modeling of the addition of an extra 0.5 m of soil cover, as a mitigation measure for the effects of climate change, indicates that the main benefit of adding this unsaturated soil was to reduce the geomembrane temperature and that this did reduce the magnitude of the increase in contaminant transport. Highlights: Geomembranes are significant in controlling hydrocarbon transport in landfill covers. Contaminant transport is modeled under current and warming Arctic soil conditions. Hydrocarbon diffusive properties for geomembranes are presented for cold temperatures. Geomembrane exhumed from Arctic landfill site shows no change in diffusive properties. This study gives new insights for future management of landfills in cold regions.